ORIGIN AND DIAGENETIC TRANSFORMATIONS OF C25 AND C30 HIGHLY BRANCHED ISOPRENOID SULPHUR COMPOUNDS: FURTHER EVIDENCE FOR THE FORMATION OF ORGANICALLY BOUND SULPHUR DURING EARLY DIAGENESIS - Kohnen M.E.L.; Damsté J.S.S.; Kock-van Dalen A.C.; De Leeuw J.W.; Haven H.L.T.; Rullkötter J. (My University, 1990)
A number of C25 and C30 highly branched isoprenoid (HBI) sulphur compounds (E.G., thiolanes, 1-oxo-thiolanes, thiophenes, and benzo[b]thiophenes) with 2,6,10,14-tetramethyl-7-(3-methylpentyl)pentadecane and 2,6,10,14,18-pentamethyl-7-(3-methylpentyl)nonadecane carbon skeletons were identified in sediments, ranging from Holocene to Upper Cretaceous. These identifications are based on mass spectral characterisation, desulphurisation, and, in some cases, by comparison of mass spectral and relative retention time data with those of authentic standards. The presence of unsaturated C25 and C30 HBI thiolanes in a Recent sediment from the Black Sea (age 3–6 × 103 a) strongly supports their formation during early diagenesis. The co-occurrence of HBI polyenes (C25 and C30) and unsaturated HBI thiolanes (C25 and C30) possessing two double bonds less than the corresponding HBI polyenes, in this Recent sediment, testifies to the formation of unsaturated HBI thiolanes by a reaction of inorganic sulphur species with double bonds of the HBI polyenes. Furthermore, a diagenetic scheme for HBI sulphur compounds is proposed based on the identification of HBI sulphur compounds in sediment samples with different maturity levels.
Keywords: Holocene; Cretaceous; Cenozoic::Quaternary::Holocene; Mesozoic::Cretaceous; Мезозой::Меловая; Кайнозой::Четвертичная::Голоцен